Rosa Liebe unterm roten Stern : zur Lage der Lesben und Schwule in Osteuropa - Hauer, Gudrun; Krickler, Kurt; Schmutzer, Dieter (Hamburg : Frühlings Erwachen, 1984)
Fonds Suzan Daniel (FSD)
Duits
Monografie